Study on Physicochemical Properties of Essential Oil from the Rhizomes of Alpinia Allughas Rosc - Nikhil Kumar; Vijayata; Shilpi Sharma (International Journal of Pharma and Bio Sciences, 2021)
Essential oil is determined as the volatile odoriferous oil obtained steam distillation of medicinal plants. The object of the study was to extract the essential oil and to determine the physicochemical properties Essential oil of Alpinia allughas was isolated by hydrodistillation has a yield of 0.18 percent by weight using Clevenger apparatus. 100 g crushed material was placed in a round bottom flask of one liter capacity for 4 hours and the essential oil was dried over anhydrous sodium sulphate. The physicochemical properties essential oil such as different specific natural products, solubility, specific gravity, refractive index, optical rotation, specific rotation, acid value, saponification value and ester value were determined, which are used to determine the quality of essential oils from plant rhizomes. To obtain much better information about the medicinally useful essential oil of the rhizome of Alpinia allughas Rosc. The oil from the rhizome collected from Guwahati, Assam. Light brown oil has a characteristic sharp odor; Semi transparent liquid state; specific gravity 0.9576; optical rotations +2°05′. The Essential oils have been in use for thousands of years dating back to ancient civilization. They have been in use perfumery from the earliest times. Their use in food flavoring and medicines can be traced to antiquity. Essential oils are so strong that a drop or two can produce significant results. They have been the active principles of many important herbal remedies since ancient times. Essential oils are the life force of the plant. In the living plant, these essential oil components are used as hormones for growth and reproduction, plant pheromones for smells which will attract pollinating insects, defense mechanisms protecting the plant from predators (herbivores and insects), and also protection against bacterial, viral, or fungal invasion. Some plants have very high concentrations of essential oils, which they have developed for protection.